Economic Sociology Perspective in Understanding Markets, Social Networks, and Institutional Roles in Economic Activity (International Journal of Economics Management and Social Science, 2026)
This article examines economic sociology perspectives on markets, social networks, and institutional roles in economic activity. Economic sociology challenges neoclassical economics' assumptions of atomized rational actors pursuing self-interest in impersonal markets, instead emphasizing that economic action is embedded in ongoing social relations and shaped by cultural meanings and institutional frameworks. Drawing on classical contributions from Weber, Polanyi, and Granovetter alongside contemporary research on social network analysis, institutional theory, and economic culture, this study analyzes how social structures and cultural understandings constitute markets rather than merely constraining rational economic behavior. The analysis explores three interconnected themes: how markets function as social institutions structured by networks, norms, and power relations; how social network position affects economic opportunities and outcomes; and how formal and informal institutions shape economic activity. Contemporary empirical evidence from studies of labor markets, financial markets, and entrepreneurship demonstrates that economic outcomes depend substantially on social capital, network embeddedness, and institutional context. This article contributes to economic sociology by synthesizing theoretical frameworks with recent empirical research, demonstrating continued relevance of sociological perspectives for understanding contemporary economic phenomena including digital platforms, gig economy, and financialization.Keywords: Economic sociology, markets, social networks, institutions, embeddedness, social capital, economic culture, market structure